Building online degrees quickly: Academic experiences and institutional benefits - McInnes, Richard; Aitchison, Claire; Sloot, Brigitte (Journal of University Teaching and Learning Practice, 2020)
Universities everywhere are rushing to upgrade their digital learning capabilities — and, more so now, in response to COVID-19. Long term, large-scale development of online courses requires investment in digital infrastructures and collaborative curriculum design involving educational, technical, and subject-matter experts. However, compared to the resources invested in course development, there is relatively little investment in researching such development processes. Drawing on findings from a study of a strategic initiative to rapidly develop 12 fully online undergraduate degree programs in one Australian university, this paper reports on a study that aimed to capture the experiences of academic course writers. Findings show broad satisfaction with the production processes, courses created, and knowledge acquired - although also demonstrating key differences between senior, junior and casualised staff. This empirical case study contributes to knowledge about capacity building arising from large-scale, in-house development of fully online degree programs.